Establishment of Aedes albopictus (Diptera: Culicidae) in the Florida Keys, 2001–2017. Issue 6 (23rd June 2018) - Murray, Heidi L; Pruszynski, Catherine A; Leal, Andrea L; Hribar, Lawrence J
Abstract: The presence of Aedes albopictus (Skuse) was first reported in the Florida Keys in 1993. Despite extensive surveillance, the Florida Keys Mosquito Control District (FKMCD) only collected specimens occasionally on a few islands, some years finding no evidence of the invasive species. In 2013–2017, FKMCD witnessed a sudden increase in population size and geographic extent of Ae. albopictus . Samples of Ae. albopictus have now been identified on 30 different islands in the Florida Keys. Three islands in particular (Key Largo, Big Pine Key, and Stock Island) have produced multiple positive samples during at least 4 of the last 5 yr, suggesting establishment of the invasive species. FKMCD continues to monitor Ae. albopictus throughout the Keys and make extensive efforts to reduce population abundance and geographic extent of this disease vector.